PENINGKATAN HASIL PEMBELAJARAN IPAS MENGGUNAKAN PROBLEM BASED LEARNING BERBANTUAN MEDIA INTERAKTIF DI KELAS V SDN 29 DADOK TUNGGUL HITAM - Zakiah, Ghina; Media, Afriza; Fitria, Yanti; Iraqi, Hana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of fifth-grade students in Science and Social Studies (IPAS) at SDN 29 Dadok Tunggul Hitam, Padang City. The problems identified included teacher-centered learning, the dominant use of the lecture method, limited use of interactive learning media, and low student learning outcomes. This study aimed to describe the improvement of students’ IPAS learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by interactive media. This study employed Classroom Action Research using qualitative and quantitative approaches. The participants consisted of one teacher and 27 fifth-grade students. The research was conducted in two cycles, each comprising four stages: planning, implementation, observation, and reflection. The data were collected through test and non-test techniques using observation sheets and achievement tests. The collected data were analyzed qualitatively and quantitatively to determine the effectiveness of the implemented learning model. The results showed that the lesson plan assessment consistently achieved 100% (Excellent) in both cycles. The teacher’s activity score improved from 89.2% (Good) in Cycle I to 96.4% (Excellent) in Cycle II. Similarly, students’ learning activity increased from 87.4% (Good) to 96.4% (Excellent). Students’ learning outcomes also improved in all domains. The affective domain increased from 66.1% to 83.3%, the psychomotor domain from 65.2% to 80.5%, and the cognitive domain from 67.2% to 88.1%. These findings indicate that the implementation of the PBL model assisted by interactive media effectively improved students’ IPAS learning outcomes in fifth grade at SDN 29 Dadok Tunggul Hitam.